(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article defines the characteristic features of the interrogation of the victim in criminal proceedings related to fraud in the context of ensuring the primary focus on providing temporary access to things and documents as soon as possible, providing thorough and comprehensive explanations to the victim by the investigator, how to protect themselves from similar fraudulent actions in the future, as well as other relevant specifics in the context of further assignment of orders to operative units, processing requests to administrators of platforms that post ads of potential fraudsters, etc.